Kajian Penanganan Anak Gelandangan Dan Pengemis Di Kota Makassar (Study on Handling of Children and Beggars in Makassar City) - Tuti Bahfiarti; Rahmat Muhammad; Aminuddin Tarawe (Jurnal Inovasi dan Pelayanan Publik Makassar, 2019)
Homeless children and beggars are a problem in big cities, including Makassar City. The problem factors that threaten street children include violence carried out by other street children, for example sexual violence; drug use, alcohol and cigarettes; and infectious diseases such as HIV/AIDS. Other potential can lead to crime, such as robbery, theft, robbery, and others in Makassar City. The research problem is the characteristics of operational actions, fostering and empowerment of homeless children and beggars based on expertise that can be developed through community development and empowerment programs of the Makassar City Government Social Service. This study can help sustain the development of homeless children and beggars in Makassar City and the Saribattang Rapid Reaction Team. The aim and target to be achieved is to find and identify the characteristics of operational actions and community development and empowerment program strategies through the Makassar City Government Social Service.The aims and targets used in a qualitative approach attempt to interpret the meaning and facts of the field, including the phenomenon of homeless children and beggars. The results showed that the operational actions of street children in Makassar City in general are family factors. The pattern of empowerment and coaching of street children through families, the policies that can be used to overcome the problem of poverty are anticipatory policies. Furthermore, the rehabilitative pattern, specifically for street children and beggars indicated there is potential for juvenile delinquency or even receiving abuse and inhaling addictive substances. Furthermore, empowerment and coaching are based on age characteristics and problems faced. Social Campaign is a way to make people aware of road users for street children and beggars to carry out educational functions. The purpose of this social campaign is to provide learning and awareness for both street children and beggars and the people of Makassar City